Forumet - matematik fråga

matematik fråga

566 0 2

Uppgift


 

sin(-3π/4)-tan(-π/4)


 

Lösning


 

sin(-3π/4)-tan(-π/4)=

 

-sin(3π/4)-tan(-π/4)=

 

-sin(π-3π/4)-tan(-π/4)=

 

-sin((1-3/4)π)-tan(-π/4)=

 

-sin((4/4-3/4)π)-tan(-π/4)=

 

-sin((4-3)π/4)-tan(-π/4)=

 

-sin(π/4)-tan(-π/4)=

 

-1/√(2)-tan(-π/4)=

 

-1/√(2)+tan(π/4)=

 

-1/√(2)+1=

 

1-1/√2=

 

√(2)/√(2)-1/√2=

 

(√(2)-1)/√2


 

Svar


 

(√(2)-1)/√2


 

Länkar


 

http://sv.wikipedia.org/wiki/Enhetscirkel

 

http://sv.wikipedia.org/wiki/Lista_%C3%B6ver_trigonometriska_identiteter

 

http://sv.wikipedia.org/wiki/Trigonometrisk_funktion